National Library of Indonesia branding strategies through ancient manuscript and rare books collection - Ali, Irhamni (2012)
The evolution of marketing strategies are changed all of theories and methods in marketing, including in libraries in marketing their products and institution. One marketing strategy that evolves today is Branding, Branding is a collection of theory and practice which aims to measure, build and manage the reputation of an institution. National Library of Republic Indonesia has a collection of 10,612 manuscripts and more than 80,000 copies of rare books, those are a great strength for the National Library Republic of Indonesia to make them as their Brand Ambassador in marketing the institution.